Analisis Penggunaan Aplikasi Kasir Pada Pelaku UMKM Kecamatan Tampan Kota Pekanbaru Riau - Wina Monalisa; Budi Prabowo (Jurnal Kendali Akuntansi, 2023)
In the era of the development of science and technology and the high level of competition in the business world is a challenge that must be faced by all parties, especially in Micro, Small and medium enterprises (MSMEs). Tampan District is one of the sub-districts in Pekanbaru City, Riau Province which is located about 10 kilometers from the center of Pekanbaru City. Many micro, small and medium enterprises (MSMEs) in Tampan, Pekanbaru have adopted technology such as the implementation of a digital cashier system to assist in managing sales transactions. The purpose of this study is to find out what digital cashier applications are predominantly used by MSME players and how influential they are for optimizing financial records. MSME players and how influential it is for optimizing financial records. The method used in this study is a qualitative method, with observational data collection techniques on MSMEs in Handsome District, Pekanbaru.